Analysis of the Influence of Entrepreneur’s Psychological Capital on Employee’s Innovation Behavior Under Leader-Member Exchange Relationship - Li, Tingyi; Liang, Wei; Yu, Zhijian; Dang, Xin (Frontiers in Psychology, 2020)
How to make use of leaders’ psychological capital to improve the innovation behavior of employees has become an important issue for the talent management of enterprises today, and it is also the goal that enterprises must pursue if they want to stand out in fierce competition. Therefore, a total of 154 enterprises in a high-tech area were selected for questionnaire survey in this study. The correlation between leader-member exchange (LMX) relationship (emotion, loyalty, contribution, and professional respect), leaders’ psychological capital (confidence, hope, optimism, and tenacity), and employees’ innovation behaviors were analyzed based on multivariate regression. Hierarchical regression method was used to examine the mediating effect of the LMX. It was found that confidence, toughness, and contribution were significantly positively correlated with employee innovation behavior (p < 0.001). The positive correlation between hope, optimism, emotion, and loyalty with employees’ innovation behavior was significant (p < 0.05). Besides, emotion, loyalty, and contribution had mediating effects on the leaders’ psychological capital and the innovation behavior of employees. In conclusion, leaders’ psychological capital can have a significant positive effect on the innovation behavior of employees directly, and it can also have an indirect positive effect on the innovation behavior of employees by maintaining high quality LMX.